Is the Advanced Pediatric Life Support formula used to calculate weight-for-age applicable to a Trinidadian population? - Ali, Khalid; Sammy, Ian; Nunes, Paula (My University, 2012)
Abstract Background In paediatric emergency medicine, estimation of weight in ill children can be performed in a variety of ways. Calculation using the and#8216;APLSand#8217; formula (weightand#8201;=and#8201;[ageand#8201;+and#8201;4] and#215; 2) is one very common method. Studies on its validity in developed countries suggest that it tends to under-estimate the weight of children, potentially leading to errors in drug and fluid administration. The formula is not validated in Trinidad and Tobago, where it is routinely used to calculate weight in paediatric resuscitation. Methods Over a six-week period in January 2009, all children one to five years old presenting to the Emergency Department were weighed. Their measured weights were compared to their estimated weights as calculated using the APLS formula, the Luscombe and Owens formula and a and#8220;best fitand#8221; formula derived (then simplified) from linear regression analysis of the measured weights. Results The APLS formula underestimated weight in all age groups with a mean difference of and#8722;1.4and#8201;kg (95% limits of agreement 5.0 to and#8722;7.8). The Luscombe and Owens formula was more accurate in predicting weight than the APLS formula, with a mean difference of and#8722;0.4and#8201;kg (95% limits of agreement 6.9 to and#8722;6.1%). Using linear regression analysis, and simplifying the derived equation, the best formula to describe weight and age was (weightand#8201;=and#8201;[2.5 x age]and#8201;+and#8201;8). The percentage of children whose actual weight fell within 10% of the calculated weights using any of the three formulae was not significantly different. Conclusions The APLS formula slightly underestimates the weights of children in Trinidad, although this is less than in similar studies in developed countries. Both the Luscombe and Owens formula and the formula derived from the results of this study give a better estimate of the measured weight of children in Trinidad. However, the accuracy and precision of all three formulae were not significantly different from each other. It is recommended that the APLS formula should continue to be used to estimate the weight of children in resuscitation situations in Trinidad, as it is well known, easy to calculate and widely taught in this setting.